2010
DOI: 10.1136/hrt.2009.186650
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in clinical presentation and surgical outcome of aortic stenosis

Abstract: Although women referred to AVR are older and more symptomatic, operative and long-term mortality are not increased. In the oldest age group of 79 years and older, women even have a better outcome, presumably due to a longer mean life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
88
3
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 23 publications
14
88
3
8
Order By: Relevance
“…In line with the majority of previous studies, we found distinctive risk profiles for men and women undergoing AVR 4, 6, 11, 12, 17, 27. Women undergoing AVR (isolated or combined) were older and had more nonatherosclerotic comorbid conditions at presentation including hypertension, diabetes mellitus, chronic obstructive pulmonary disease, atrial fibrillation/flutter, and anemia compared with men.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with the majority of previous studies, we found distinctive risk profiles for men and women undergoing AVR 4, 6, 11, 12, 17, 27. Women undergoing AVR (isolated or combined) were older and had more nonatherosclerotic comorbid conditions at presentation including hypertension, diabetes mellitus, chronic obstructive pulmonary disease, atrial fibrillation/flutter, and anemia compared with men.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding disparity in referral for testing, women with AS were less likely to be seen by a specialist and less likely to be referred for testing 19. Regarding disparity in referral to surgery, women diagnosed with AS had unfavorable preoperative baseline characteristics compared with men at the time of presentation and thus were less likely to be referred to surgical treatment 4, 9, 24. Interestingly, this disparity in referral to valve replacement is not seen with the current TAVR practice; in the United States and Germany, women composed 52% and 55%, respectively, of all patients undergoing TAVR, respectively 25, 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuchs et al reported a lower mortality in women after AVR in the ≥79-years age group. 21 In the present study, sex-related differences in survival after AVR in the elderly were also observed in those aged ≥65 years (data not shown). Adjusted 5-year mortality risk of male relative to female patients, however, was neutral, suggesting that the better crude survival rate in women was related to the lower prevalence of measured morbidities in women.…”
Section: Discussionsupporting
confidence: 48%
“…Morris et al reported increased short-term mortality in women, 19 whereas other reports have indicated better longterm survival in women 21 or no sex-related differences in outcomes. 22 These varying results may be explained by the differences in comorbidities contributing to mortality risks.…”
Section: Discussionmentioning
confidence: 63%